Armies of War Without Uniforms: Mercenaries and Private Military Companies in Russia’s Interventions in Syria and Ukraine - Çağla Mavruk; Ali Gök (Cumhuriyet Üniversitesi İktisadi ve İdari Bilimler Dergisi)
In the struggle for influence and power between states, states tend to use mercenaries and PMCs due to reasons such as the economic cost of the regular army, the negative reactions to be received from many actors in an official intervention in the target state, the sanctions of international law and the indignation caused by a possible loss of official soldiers, especially in the society. The history of mercenaries dates back to ancient times. However, they were used extensively in conflicts in many regions after the Cold War. The changing perception of security is the main reason for the resurgence of mercenary activities. Factors at the center of the changing perception of security are the end of the Cold War and the emergence of a privatized military industry. Considering the interventions where mercenaries were deployed, Russia’s interventions in Ukraine in 2014 and then in 2022 and in Syria in 2015 come into prominence. The overarching purpose of this research is to explain how these actors affect the character of the war by explaining the reasons for their use, duties and effects on the battlefield. The study concludes that Russia used mercenaries in Ukraine for secrecy and reasonable deniability and aimed to prevent the reaction of the world public opinion. On the other hand, Russia used mercenaries in Syria to prevent the reaction of the Russian public by hiding casualties and reflecting the operation as a successful operation without any casualties.